1H NMR application in characterizing the refinery products of gasoline. (6th June 2017) - Sun, Cheng; Wang, Zhixiao
Abstract: We report on an application of 1 H NMR spectroscopy in characterizing the gasoline properties of its refinery products. In this work, a variety of gasoline samples obtained from different refinery stages are studied, and the aromatic, olefin, and paraffin contents as well as the octane number (ON) of the gasoline samples are characterized by 1 H NMR. The properties of two product gasoline samples are also studied by 1 H NMR spectroscopy; the NMR‐determined values for the ONs are compared with the research octane number values measured in a standard test engine, and a good agreement is achieved. This work indicates that the characteristics of gasoline can be revealed by 1 H NMR, and the values derived from the NMR spectroscopy can be used to assess the gasoline quality during its refinery processes. Based on this work, we demonstrate that the 1 H NMR spectroscopy is a convenient tool in the continuous monitoring of the refinery processes of gasoline.